KARAKTERISTIK, MEKANISME AKSI, DAN EFIKASI VAKSIN DALAM VAKSINASI GLOBAL PANDEMI COVID-19 - M. Rakha Gerizha; Ade Yonata; Syazili Mustofa (Prodi Kedokteran Fakultas Kedokteran Universitas Malahayati, 2022)
Abstract: Characteristics, Mechanism of Action, and Efficacy of Vaccine in The Global Vaccination of The Covid-19 Pandemic. This review considers vaccines developed against SARS-CoV-2 in the period of the Covid-19 pandemic. In this search, we will discuss the mechanism of action of each vaccine as well as its efficacy and safety. Four vaccines are currently in common use in various countries: Pfizer-BioNTech (USA), Moderna (USA), Astra-Zeneca (UK), and Janssen Johnson & Johnson (USA). In addition, there are two vaccines that are only used by a few countries: Novavax (USA) and SInovax (China) for which data are not widely studied. Pfizer and Moderna's efficacy for preventing disease or severe illness was 95–87.5% and 94.5–100%, respectively. The efficacy of Astra-Zeneca and Janssen Johnson & Johnson are around 70% and 57-72%, respectively. Meanwhile, Sinovax and Novavax vaccines have efficacy of about 65-90% and 60-89.7%, respectively, for prevention against Covid-19. The vaccination strategy is based on accelerating the administration of vaccines, so that as many subjects as possible can be vaccinated quickly to achieve herd immunity. Keywords: COVID-19, effectiveness, efficacy, SARS-CoV-2, and vaccine